2019
DOI: 10.3390/s20010074
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-x/TiO2-Structure Based ‘Self-Heated’ Sensor for the Determination of Some Reducing Gases

Abstract: In this research we report the gas-sensing properties of TiO2-x/TiO2-based hetero-structure, which was ‘self-heated’ by current that at constant potential passed through the structure. Amperometric measurements were applied for the evaluation of sensor response towards ethanol, methanol, n-propanol and acetone gases/vapours. The sensitivity towards these gases was based on electrical resistance changes, which were determined by amperometric measurements of current at fixed voltage applied between Pt-based cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 63 publications
2
78
0
Order By: Relevance
“…The stress could induce the phase transition from the amorphous phase to the anatase phase [32]. In addition, titanium might possibly be left as residual metallic phase without being oxidized, and the stoichiometric composition could be changed during the oxidation when the layer is too thick [33]. The implied V oc results of the oxidized 2 nm titanium layer showed a similar trend as the lifetime data.…”
Section: Electronic and Optical Characteristics Of Oxidized Titanium supporting
confidence: 53%
“…The stress could induce the phase transition from the amorphous phase to the anatase phase [32]. In addition, titanium might possibly be left as residual metallic phase without being oxidized, and the stoichiometric composition could be changed during the oxidation when the layer is too thick [33]. The implied V oc results of the oxidized 2 nm titanium layer showed a similar trend as the lifetime data.…”
Section: Electronic and Optical Characteristics Of Oxidized Titanium supporting
confidence: 53%
“…Working at a high temperature requires more sophisticated and expensive sensor construction and additional equipment for regulation of temperature in order to get a stable sensor response, which eventually leads to high power consumption. Therefore, in recent years, low-temperature gas sensors based on light-activated metal oxide semiconductors have attracted a lot of attention [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. It was suggested that light affects gas sensor performance in the following ways: (1) light influences dissociation of oxygen species and, consequently, the adsorption of VOC-based analyte molecules; (2) light increases density of free electron–hole pairs and facilitates carrier generation, thus enabling the sensor to work at room temperature with high sensitivity and selectivity [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 4 the temperature variation of the normalized electrical resistances of the three samples are presented. The normalization was performed with respect to the resistance at around 296 K. Recently, similar metallic temperature dependence of the electrical resistance has been reported in an intermediate temperature range, 50-200 K, for other oxide heterostructures [29].The variation of the critical transition temperature, Tc, as a function of the pyrolysis temperature is shown in the inset of Figure 4. The Tc of the superconducting films increases with the increase of pyrolysis temperature, from 88.2 K for the sample pyrolyzed at 500 °C to 90.7 K in the case of the 650 °C treated film.…”
Section: Resultsmentioning
confidence: 55%